Eradication of Mycoplasma pneumoniae biofilm towers by treatment with hydrogen peroxide or antibiotic combinations acting synergistically - Rasha A. Fahim; Zoë E. D. Rodriguez; Zachery Oestreicher; Nathan R. Schwab; Natalie E. Young; Kavita Shrestha; Mitchell F. Balish (PLoS ONE, 2025)
Mycoplasma pneumoniae is an important chronic, asthma-associated pathogen that is increasingly antibiotic-resistant. These bacteria have highly reduced genomes and lack a cell wall and numerous other antibiotic targets. They form biofilm towers after prolonged growth both axenically and on tissue culture cells. The biofilm towers have features associated with chronic infection: they are highly resistant to erythromycin and have substantially increased resistance to complement, although they are sensitive to a combination of the two. This work sought to characterize the profile of agents that could eradicate M. pneumoniae biofilm towers. Biofilm towers were found to provide no defense against H2O2, an M. pneumoniae virulence factor whose production is severely attenuated during biofilm tower growth. Checkerboard assays revealed that dual combinations of erythromycin, moxifloxacin, and doxycycline acted synergistically against two strains of M. pneumoniae. Crystal violet assays suggested that pairs of these agents, when used at clinically relevant concentrations, had substantial efficacy against pre-formed biofilm towers, but scanning electron microscopy revealed that the eradication of biofilm towers was even more complete than crystal violet assays indicated. Although the use of fluoroquinolones and tetracyclines in children, who are the most frequently infected population, is not preferred over macrolides due to potential side effects, this work shows that synergistic interactions among therapeutic agents provide potential clinical paths to substantially reducing or eradicating M. pneumoniae biofilms, thereby decreasing morbidity. Furthermore, the sensitivity to H2O2 suggests that small-molecule therapeutics may also be suitable for biofilm clearance.